Automated news article summarizer - Dapulano, Gerardo Jr. E.; Serrano, Paul John M.; Solomon, Marco Carmelo C. (2002)
In this paper, we describe our CS 198 Project, the Automated News Article Summarizer. Limited to online World News text articles only, this summarizer utilizes the algorithms presented by Barzilay and Elhadad in their paper Using Lexical Chains for Text Summarization (1997) [2]. We discuss in detail these techniques and methods, primarily Text Segmentation, Lexical Chains Computation and Sentence Selection and Extraction. The summarizer also uses the Word/Net Lexical Database as its knowledge for word sense disambiguations and a Part-of-Speech Tagging Algorithm for the selection of candidate words from the input text. The algorithms used are based on shallow Linguistic Analysis Approach, which does not require a full semantic interpretation of the texts to produce its summary. Also presented here are the pitfalls and strong points of these algorithms, and how they function collectively to deliver the desired results.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Automatic abstracting; Lexicology -- Data processing; Semantics -- Data processing